STAR AND POOR FUND PHENOMENA IN ISLAMIC- AND CONVENTIONAL-FOCUSED FAMILIES: EMERGING COUNTRY EVIDENCE - Bani Atta, Anas Ahmad; Marzuki, Ainulashikin (Journal of Islamic Monetary Economics and Finance, 2021)
The aim of this study is to investigate star and poor phenomena and their impact on the flows of Islamic-focused family (IFF) and conventional-focused family (CFF). The sample includes the four emerging countries with the largest number of Islamic mutual funds from 2007 to 2018 (Saudi Arabia, Malaysia, Indonesia, and Pakistan). Panel regression analysis was used to examine the impact of dummy star and poor as independent variables, and family age, size, number of funds, past returns, and total risk as control variables for fund family flows. The results show that the dummy star has a significantly positive relationship with family flows. Family managers have succeeded in attracting more investors by using the strategy of advertising the best performing funds. However, in both, all families and IFF, the dummy poor has a negative relationship, but is insignificant. On the other hand, for CFFs, the dummy poor is significantly negative. This is because investors in IFFs, unlike those in CFFs, have more loyalty due to their moral and religious goals in addition to traditional goals. The novel finding of the study is the difference in the star phenomenon between the IFF and CFF. The findings are important for managers, as they will help them to create appropriate strategies to attract more flows and increase the assets under their management. In addition, the findings will help investors to direct their money to appropriate families.